Numerical Modelling of Clay Seal Maturation in Deep Boreholes with Nuclear Waste - Ting Yang; Hans Mattsson; Roland Pusch; Jan Laue; Sven Knutsson; Xiaodong Liu (Advances in Materials Science and Engineering)
One of the major challenges of high-level nuclear waste (HLW) isolation in deep boreholes is to anticipate the maturation behaviour of swelling clay when the waste, surrounded by dense clay encased in perforated tubes, is submerged into the borehole mud. The ultimate homogeneity of this clay seal acting as a barrier is expected to stabilize the borehole and to prevent possible leakage of radioactivity. In this study, a numerical model for predicting the maturation of the clay barrier has been developed. In the model, the water transport is controlled by the differences in the suction potential and the permeability. The model is able to simulate the maturation process, both the expeditious water transport and the clay migration into the surrounding mud, from beginning to end. Results from laboratory tests of the clay maturation were compared with the predictions made by the model. They are in good agreement, but refinement is proposed by taking the impact of the tube perforation on the maturation rate into more consideration. The proposed numerical model will also be useful in selecting a suitable design for clay barriers in HLW boreholes. Different combinations of clay dimensions and initial densities of mud and dense clay can thus be studied to determine the final homogenization and the end densities.